KORELASI KETERAMPILAN MEMBACA PEMAHAMAN DENGAN KETERAMPILAN MENULIS TEKS EKSPLANASI SISWA KELAS XI SMA ADABIAH PADANG - Oktiana, Putri Kartika; Afnita, Afnita (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
ABSTRACT The purpose of this study is three. First, describe comprehension reading skills. Second, describe explanatory text writing skills. Third, describe the correlation of reading comprehension skills with explanatory text writing skills of class XI students of SMA Adabiah Padang. This type of research is quantitative with descriptive method. The design of this study is correlational design. The study population was registered in 2018/2019, which is 287 students. The research sample was proportional random sampling of 20% of the population of 57 students. The research data is in the form of scores on the results of comprehension reading skills tests and scores on the results of explanatory text writing skills. The instrument of this study was an objective test to measure comprehension reading skills and performance tests to measure writing skills. The results of this study are three. First, reading comprehension skills of class XI students of SMA Adabiah Padang are of good qualification (B). Second, explanatory text writing skills of class XI students of SMA Adabiah Padang are of good qualification (B). Third, there is a correlation of reading comprehension skills with explanatory text writing skills with n-1 freedom degrees at the 95% confidence level. The value of tcount (38.54) is greater than t table (1.66) that is tcount> ttable (38.54> 1.68) thus H0 is rejected and H1. Based on the results of these studies it was concluded that reading comprehension skills correlated with explanatory text writing skills.  Kata Kunci: Korelasi, Keterampilan Membaca Pemahaman, Keterampilan Menulis Teks Eksplanasi.